2022
DOI: 10.1101/2022.01.28.22270035
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Phase 2 Randomized, Double-Blind, Placebo-controlled Trial of Oral Camostat Mesylate for Early Treatment of COVID-19 Outpatients Showed Shorter Illness Course and Attenuation of Loss of Smell and Taste

Abstract: Importance: Early treatment of mild SARS-CoV-2 infection might lower the risk of clinical deterioration in COVID-19. Objective: To determine whether oral camostat mesylate would reduce upper respiratory SARS-CoV-2 viral load in newly diagnosed outpatients with mild COVID-19, and would lead to improvement in COVID-19 symptoms. Design: From June, 2020 to April, 2021, we conducted a randomized, double-blind, placebo-controlled phase 2 trial. Setting: Single site, academic medical center, outpatient setting in C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 14 publications
2
18
0
Order By: Relevance
“…Additionally, a US study of outpatients treated with camostat mesilate at a dose of 200 mg four times daily for 7 days did not achieve a reduction in viral load compared with placebo [24]. Interestingly, the efficacy of camostat mesilate was not confirmed by the primary endpoint of viral load, but camostat mesilate prevented the loss of smell/taste compared with placebo.…”
Section: Discussionmentioning
confidence: 98%
“…Additionally, a US study of outpatients treated with camostat mesilate at a dose of 200 mg four times daily for 7 days did not achieve a reduction in viral load compared with placebo [24]. Interestingly, the efficacy of camostat mesilate was not confirmed by the primary endpoint of viral load, but camostat mesilate prevented the loss of smell/taste compared with placebo.…”
Section: Discussionmentioning
confidence: 98%
“…The trial did not, however, achieve the primary endpoint of reducing the viral load by PCR in the upper respiratory tract. 34 …”
Section: Resultsmentioning
confidence: 99%
“…A clinical trial on 95 patients who received 200 mg of camostat mesylate three times per day for 2 weeks for the treatment of dyspepsia associated with non-alcoholic mild pancreatic disease demonstrated only mild adverse effects [ 143 ], indicating that this drug is well tolerated [ 29 ]. A clinical trial demonstrated a more rapid resolution of COVID-19 symptoms and amelioration of lost taste and smell in outpatients with newly diagnosed mild COVID-19 infection who received oral camostat mesylate [ 30 ]. Nafamostat mesylate is a synthetic serine protease that is clinically approved in Japan to treat disseminated intravascular coagulation and acute pancreatitis.…”
Section: Therapeutic Strategies Targeting the Tmprss2 Receptormentioning
confidence: 99%
“…Nafamostat mesylate and camostat mesylate are synthetic serine protease inhibitors with the ability to impair viral entry. In a clinical trial involving newly diagnosed outpatients with mild infection, oral camostat mesylate was shown to reduce the viral load of respiratory SARS-CoV-2, leading to rapid resolution of symptoms related to COVID-19 and amelioration of loss of smell and taste [ 30 ]. Thus, precise information about the functions of the TMPRSS2 receptor could aid in the development of therapeutic strategies against COVID-19 and its related complications, including anosmia.…”
Section: Introductionmentioning
confidence: 99%